Influence of Organic Acids from the Oral Biofilm on the Bond Strength of Self-Etch Adhesives to Dentin - Amaral,Cristiane Mariote (2015)
Abstract: The aim of this study was to evaluate the microtensile bond strength of self-etch adhesive systems to dentin after storage in acids from oral biofilm. Three adhesive systems were used in the study: a two-step self-etch adhesive for use with a silorane-based resin composite (Filtek P90 adhesive system - P90), a two-step self-etch adhesive (Clearfil SE Bond - CSE) and a one-step self-etch adhesive (Adper Easy One - AEO). The bond strength of these products was evaluated by bonding resin composite (Filtek Z350 for CSE and AEO; and Filtek P90 for P90) to 90 bovine dentin tooth fragments, according to the manufacturer's instructions. After 24 h of water storage at 37 °C, the specimens were sectioned into beams (1 mm2) divided and stored in distilled water, lactic acid and propionic acid, for 7 and 30 days. After storage, the specimens were tested for microtensile bond strength. Data were analyzed by three-way ANOVA and Tukey´s test (α=0.05). CSE presented the highest microtensile bond strength after storage in distilled water for 7 and 30 days. The microtensile bond strength of all adhesive systems was lower after storage in lactic acid and propionic acid than after water storage. Significant difference was not found between storage times.